The Effect of e-WOM Dimensions on Online Repurchase Intention: Survey on Generation Z (12 to 27 Years Old) of Online Travel Agent Users in Indonesia - Nuraeni, Ita; Manoarfa, Hilda (Budapest International Research and Critics University, 2022)
e-WOM is one of the media used by Online Travel Agent (OTA) companies in increasing purchase intention. OTA is a company engaged in services that help potential consumers in traveling activities, like transportation and lodging services. Each OTA company has its own method of presenting content on its website. The method of collecting information is through a literature study, which aims to determine the effect of e-WOM on purchase intention on OTA in Indonesia. e-WOM has a different effect on purchase intention. In OTA Traveloka, e-WOM has a significant effect on purchase intention, but on OTA Agoda it does not have a significant effect.